Coupling of hormonal stimulation and transcription via the cyclic AMP-responsive factor CREB is rate limited by nuclear entry of protein kinase A. - Masatoshi Hagiwara; Paul K. Brindle; A Harootunian; Robert Armstrong; J Rivier; W Vale; Richard W. Tsien; Marc Montminy (1993)
Cyclic AMP (cAMP) regulates a number of eukaryotic genes by mediating the protein kinase A (PKA)-dependent phosphorylation of the CREB transcription factor at Ser-133. In this study, we test the hypothesis that the stoichiometry and kinetics of CREB phosphorylation are determined by the liberation and subsequent translocation of PKA catalytic subunit (C subunit) into the nucleus. Using fluorescence imaging techniques, we observed that PKA was activated in a stimulus-dependent fashion that led to nuclear entry of C subunit over a 30-min period. The degree of CREB phosphorylation, assessed with antiserum specific for CREB phosphorylated at Ser-133, correlated with the amount of PKA liberated. The time course of phosphorylation closely paralleled the nuclear entry of the catalytic subunit. There was a linear relationship between the subsequent induction of the cAMP-responsive somatostatin gene and the degree of CREB phosphorylation, suggesting that each event--kinase activation, CREB phosphorylation, and transcriptional induction--was tightly coupled to the next. In contrast to other PKA-mediated cellular responses which are rapid and quantitative, the slow, incremental regulation of CREB activity by cAMP suggests that multifunctional kinases like PKA may coordinate cellular responses by dictating the kinetics and stoichiometry of phosphorylation for key substrates like CREB.